IMPACT OF AGROTECHNICAL FACTORS ON SOYBEAN YIELDS - Milenko, О.; Solomon, Yu.; Veherenko, V. (Scientific Progress & Innovations, 2022)
Due to the growing demand for protein sources, it is expedient to reorganize the structure of crops in Ukraine to expand the areas of soybean crops. This crop can solve the problem of protein while increasing the fertility of the soil and improving its nitrogen balance. An essential condition for the high productivity of soybean crops is the correct choice of sowing dates, optimal feeding area, placement scheme, and density of plants in crops. The research aimed to estimate the influence of sowing dates and seed sowing rates on the length of the growing season and the yield of soybeans. The research was conducted during 2019–2021. The object of the research was the early ripening variety Zlatoslava, which was sown according to three rates of sowing seeds: 700,000 per ha, 800,000 per ha, 900,000 per ha, and the following sowing dates: the first – April 23, the second – May 3, the third – May 13. We found out that it is necessary to determine the optimal seeding rate for each variety in the conditions of the corresponding growing zone and to relate it to the structure of the sown areas, the place of soybeans in the crop rotation, and the timing of sowing, which is caused by climate changes. During the field experiment, with the help of phenological observations, it was revealed that the maturity of soybean plants occurred much earlier under the condition of sowing the crop in the second and third sowing periods, the sowing rates did not significantly affect the duration of the growing season of soybean plants of the Zlatoslava variety. We observed a significant change in the duration of the growing season as a result of the influence of the weather conditions of the research year. In 2019 and 2021, the vegetation period of the crop was longer on average by 5 days for all variants of the experiment compared to 2020. Crop yield was higher in options with crop sowing in the first decade of May with a seed sowing rate of 800,000 per ha. Sowing crops in the second decade of May had better impact on crop productivity with a thickened agrocenosis. Therefore, for production crops, we recommend sowing soybeans with early-ripening varieties in the first decade of May with a seed sowing rate of 800,000 per ha. In later periods of sowing, it is necessary to increase the seed sowing rate to 900,000 per ha.